2016
DOI: 10.1158/1055-9965.epi-15-0924
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Consumption and the Risk of Colorectal Cancer

Abstract: Background Coffee contains several bioactive compounds relevant to colon physiology. Although coffee intake is a proposed protective factor for colorectal cancer (CRC), current evidence remains inconclusive. Methods We investigated the association between coffee consumption and risk of CRC in 5,145 cases and 4,097 controls from the Molecular Epidemiology of Colorectal Cancer (MECC) study, a population-based case-control study in northern Israel. We also examined this association by type of coffee, by cancer … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 29 publications
0
51
0
2
Order By: Relevance
“…The largest prospective studies that suggested an inverse relationship between coffee consumption and glioma risk used combined coffee and tea intake . The null association between coffee consumption and glioma is somewhat surprising given the previously observed inverse associations between coffee intake and other cancers and beneficial effects on cardiometabolic health; however, other studies have revealed that glioma risk factors appear to differ from those for other cancers, such as smoking …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The largest prospective studies that suggested an inverse relationship between coffee consumption and glioma risk used combined coffee and tea intake . The null association between coffee consumption and glioma is somewhat surprising given the previously observed inverse associations between coffee intake and other cancers and beneficial effects on cardiometabolic health; however, other studies have revealed that glioma risk factors appear to differ from those for other cancers, such as smoking …”
Section: Discussionmentioning
confidence: 96%
“…Increased consumption of tea and coffee, two of the most popular beverages worldwide, has been associated with decreased risk of cancers of several sites in human studies. [1][2][3][4][5][6][7][8][9][10] Less is known about the association between tea or coffee consumption and risk of glioma, a cancer for which few lifestyle factors have been identified. 11,12 Coffee is a rich source of caffeine, and both tea and coffee contain additional biologically active compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have generally found no connection between coffee and an increased risk of heart disease or cancer [45,46]. In fact, a few studies have found an association between coffee consumption and decreased overall mortality and possibly cardiovascular mortality, although the suggestion is not a fact in young aged people who consume large amounts of coffee [23, 67,68]. High doses of coffee intake during pregnancy increase the risk of miscarriage, independent of pregnancyrelated symptoms [69].…”
Section: Health Risks Of Coffee Consumptionmentioning
confidence: 99%
“…It has nutraceutical approach that can able to reduce colorectal cancer [11,20,43,45,68,102] The caffeine can significantly improve our physical performance Through reducing rating of perceived exertion during and after exercise [103][104][105][106] Coffee consumption can fight stress and make active our brain and it has beneficial influence on mood, cognitive function, performance and hydration Through improvements in physical endurance, cognitive function, particularly alertness and vigilance, mood and perception of fatigue.…”
Section: Health Benefit Of Coffee Consumption Description Of Action Smentioning
confidence: 99%
“…Coffee consumption may also reduce the risk of colon cancer (Schmit et al . ), does not increase hypertension (Rhee et al . ) nor cancer risk (Arab ) and may be protective against cardiovascular disease (Crippa et al .…”
Section: Human Intervention Studies On Hydroxycinnamic Acids and Coffeementioning
confidence: 99%